Analytical design of the missile control device to intercept aerodynamic target - Markevich, V. E.; Legkostup, V. V. (Sistemnyĭ analiz i prikladnai͡a︡ informatika., 2019)
The analytical method of synthesis of devices for joint optimal estimation of parameters and control of the state of nonlinear dynamic stochastic objects is considered. A brief review of the existing and promising methods of missile guidance, as well as a comparative description of the advantages and disadvantages. Methods of improving accuracy and jamming-resistance methods of guidance, one of which is an approach based on joint estimation and state control of nonlinear object with random driving and interfering influences. The main directions of research on this subject, including statistical synthesis of the optimal control system, estimation of the potential characteristics of the designed system, analysis of the structure of the optimal system and evaluation of its simplification, the formation of quasi-optimal structures of the control system, evaluation of the criticality (sensitivity) of the system characteristics to changes in a priori information. The choice of the invariant immersion method for the analytical design of the structure of the optical evaluation-control device is substantiated. Analytical expressions describing the algorithm of functioning of the device of joint estimation and control of the state of a multidimensional nonlinear multi-connected object are given.